Effect of 12-Week Corrective Training on Lumbar Multifidus Muscle Asymmetry and Pain Intensity in Veterans With One-sided Below-knee Amputation Suffering From Chronic Low Back Pain - E. Faraji; A.H. Barati; H. Sadeghi; H.R. Fateh; M. Allami; M.R. Soroush (Afarand Scholarly Publishing Institute, 2018)
Aims: Asymmetry while walking in people with lower limb amputation induces asymmetry in muscular activity, fatigue, instability in the spine cord, and low back pain. The aim of this study was to assess the effect of 12-week corrective training on lumbar multifidus muscle asymmetry and pain intensity in veterans with one-sided below-knee amputation suffering from chronic low back pain. Materials & Methods: In this semi-experimental study with pre-test post-test design, 20 male veterans with one-sided below-knee amputation at Kowsar orthosis and prosthesis center in Tehran, Iran were selected by voluntary sampling method in 2016. After the initial assessment of the individuals, the selected training was taught to the veterans. The training program was performed during 12 weeks (5 days per week). After completing the training period, the electromyography of multifidus muscles and pain intensity assessment were performed again. Muscle asymmetry was measured in activity of maximum voluntary contraction of the muscles and muscular endurance (Sorenson test). Data were analyzed by dependent t-test. Findings: Compared with the pre-test, in the post-test, pain intensity significantly decreased, and significant increase was observed in maximum contraction of the lumbar multifidus muscle of the amputation side (p<0.05); however, multifidus muscle asymmetry did not change significantly in maximum muscle contractility and muscular endurance (p>0.05). Conclusion: The corrective training has a positive effect on the pain intensity in male veterans with one-sided below-knee amputation suffering from chronic low back pain, but it does not affect multifidus muscle asymmetry in maximum contraction of muscle and muscular endurance.